Redescription of three species of apobaetis day, 1955 (Ephemeroptera: Baetidae) - Cruz, Paulo Vilela (Zootaxa, 2020)
The genus Apobaetis Day is one of the few lineages of the family Baetidae distributed throughout the continental Americas. Three very similar species of this genus-Apobaetis etowah (Traver), Apobaetis signifer Lugo-Ortiz & McCaffety, and Apobaetis fiuzai Salles & Lugo-Ortiz-have important morphological details, pertinent to species identification, that remain to be described. This lack of detailed taxonomic information has resulted in ample misdiagnoses of the species, particularly regarding A. fiuzai in South America. In fact, almost all the recently collected specimens have been assigned to this species. The present study aimed to establish a new morphological diagnosis of these three Apobaetis species through a redescription of their larvae, based on type material, and the proposition of a new identification key for larvae of this genus. The review of the type specimens supports two conclusions: (i) that A. etowah, A. signifer, and A. fiuzai are highly similar, yet can be considered as distinct species, and (ii) the previous diagnoses and keys do not effectively separate A. fiuzai from A. signifer. © 2020 Magnolia Press
Keywords: Aquatic insect; Key; Neotropics; Types